GSA BULLETIN FPMR D-102 PUBLIC BUILDINGS AND SPACE - ROUSH,LF (Tufts Archival Research Center, 2007)
General Services Administration (GSA) bulletin notifying federal agencies of GSA guidelines for smoking in public areas and large working areas. Provides background on issue and discusses the rights of employees. Discusses required actions and details guidlelines.